EFEKTIFITAS PENERAPAN HUKUM TERHADAP KEJAHATAN PENCABULAN ANAK (STUDI KASUS POLRESTABES MEDAN) - Hafiz, Muhammad Fiqih; Sitompul, Muhammad Nasir (Legal Standing : Jurnal Ilmu Hukum, 2024)
Child molestation is a form of sexual violence that is increasingly concerning in Indonesia. Cases involving child molestation often have long-lasting psychological, physical, and social impacts on the victims. The number of child molestation cases in Medan City has continued to increase in recent years. This indicates a failure in various prevention and handling efforts made by the authorities. This study analyzes the extent to which the application of the law in child molestation cases at the Medan Police Headquarters is effective in reducing the number of child molestation crimes. This study is a normative-empirical legal study that is descriptive analysis in nature. The approaches used in this study include the statutory regulatory approach and the case approach. Secondary data were obtained through literature study techniques using data collection tools in the form of document studies. In addition, this study is also supported by field data collected through field study techniques by interviewing the Medan City Police Headquarters. The effectiveness of its application in the field often experiences obstacles. The results of the analysis show that there are serious efforts by the police to handle child molestation cases, but there are still obstacles in maximum law enforcement. These obstacles can be related to legal interpretation, availability of evidence, and the process of proof in court. As the main institution in handling child molestation cases. The effectiveness of the application of criminal law against perpetrators of child molestation crimes in Medan City, based on the role of the Medan Police, is greatly influenced by various factors, including limited resources, coordination between institutions, and social stigma that hinders case reporting. There are still challenges in the investigation and prosecution process, such as the difficulty of collecting evidence and complicated legal procedures, affecting the resolution of child molestation cases.